2012
DOI: 10.2807/ese.17.25.20203-en
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Chlamydia trachomatis endocervical infection in a previously unscreened population in Rome, Italy, 2000 to 2009

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Table S2 (ESM1) shows the detailed characteristics of the selected studies with Ct infection risk estimates in HPV-positive women. Among the 19 selected studies, 9 articles estimate the risk of Ct infection in HPV-positive women without classifiable genotypes (Fogue et al 2018;Enthumathi et al 2015;Panatto et al 2015;Marcone et al 2012;Finan et al 2006;Ta ´bora et al 2005;Baldwin et al 2004;da Silva et al 2004;Tamim et al 2002), 4 consider Ct infection risk in women with HR-HPV infection (Harder et al 2016;Aghaizu et al 2014;Yin et al 2013;Oh et al 2009), 3 consider Ct infection risk among women with infection by HR-HPV and LR-HPV (Safaeian et al 2010;Pereira et al 2010;Franceschi et al 2007), one evaluates the Ct infection risk among women infected with nonclassifiable HPV genotypes, HR-HPV and LR-HPV, single and multiple infection (Molano et al 2003), one considers the Ct infection risk in women with history of non-classifiable HPV genotypes infection (Hwang et al 2014) and one estimates Ct infection risk among women with HR-HPV multiple infections (Quino ´nez-Calvache et al 2016). We classified the studies considering the HPV prevalence (Bruni et al 2010) in the study location: 10 studies were categorized as ''low prevalence countries'' (Harder et al 2016;Panatto et al 2015;Aghaizu et al 2014;Enthumathi et al 2015;Hwang et al 2014;Yin et al 2013;Marcone et al 2012;Oh et al 2009;Finan et al 2006;Tamim et al 2002) and 7 as ''high prevalence countries'' (Fogue et al 2018;Quino ´nez-Calvache e...…”
Section: Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S2 (ESM1) shows the detailed characteristics of the selected studies with Ct infection risk estimates in HPV-positive women. Among the 19 selected studies, 9 articles estimate the risk of Ct infection in HPV-positive women without classifiable genotypes (Fogue et al 2018;Enthumathi et al 2015;Panatto et al 2015;Marcone et al 2012;Finan et al 2006;Ta ´bora et al 2005;Baldwin et al 2004;da Silva et al 2004;Tamim et al 2002), 4 consider Ct infection risk in women with HR-HPV infection (Harder et al 2016;Aghaizu et al 2014;Yin et al 2013;Oh et al 2009), 3 consider Ct infection risk among women with infection by HR-HPV and LR-HPV (Safaeian et al 2010;Pereira et al 2010;Franceschi et al 2007), one evaluates the Ct infection risk among women infected with nonclassifiable HPV genotypes, HR-HPV and LR-HPV, single and multiple infection (Molano et al 2003), one considers the Ct infection risk in women with history of non-classifiable HPV genotypes infection (Hwang et al 2014) and one estimates Ct infection risk among women with HR-HPV multiple infections (Quino ´nez-Calvache et al 2016). We classified the studies considering the HPV prevalence (Bruni et al 2010) in the study location: 10 studies were categorized as ''low prevalence countries'' (Harder et al 2016;Panatto et al 2015;Aghaizu et al 2014;Enthumathi et al 2015;Hwang et al 2014;Yin et al 2013;Marcone et al 2012;Oh et al 2009;Finan et al 2006;Tamim et al 2002) and 7 as ''high prevalence countries'' (Fogue et al 2018;Quino ´nez-Calvache e...…”
Section: Selected Studiesmentioning
confidence: 99%
“…Thirteen are cross-sectional studies (Fogue et al 2018;Harder et al 2016;Enthumathi et al 2015;Panatto et al 2015;Aghaizu et al 2014;Yin et al 2013;Marcone et al 2012;Pereira et al 2010;Oh et al 2009;Franceschi et al 2007;Finan et al 2006;Ta ´bora et al 2005;Baldwin et al 2004), 3 are cohort studies (Quino ´nez-Calvache et al 2016;Hwang et al 2014;Molano et al 2003), 2 are case-control studies (da Silva et al 2004;Tamim et al 2002) and 1 is a nested case-control study (Safaeian et al 2010). Ten studies were published until 2010 (Tamim et al 2002;Molano et al 2003;Baldwin et al 2004;da Silva et al 2004;Ta ´bora et al 2005;Finan et al 2006;Franceschi et al 2007;Oh et al 2009;Pereira et al 2010;Safaeian et al 2010) and 9 after 2010 (Marcone et al 2012;Yin et al 2013;Hwang et al 2014;Aghaizu et al 2014;Panatto et al 2015;Enthumathi et al 2015;Quino ´nez-Calvache et al 2016;Harder et al 2016;Fogue et al 2018). Eight studies investigated the risk of chlamydia in HPV-positive women aged less than 36 years …”
Section: Selected Studiesmentioning
confidence: 99%
“…The susceptibility of all age groups to C. trachomatis infection was also supported by the similar CT incidence among different age groups in our study. In general, C. trachomatis incident cases ( Scott Lamontagne et al, 2007 ; Walker et al, 2012 ; Silver et al, 2015 ) and NAAT-positive detections ( Marcone et al, 2012 ; Sonnenberg et al, 2013 ) are more often found in teenagers (15–19 years) and declined with age thereafter. Two studies based on seroconversions also reported that the highest incidence occurred in those under 26 years in New Zealand ( Righarts et al, 2017 ) and pregnant women under 23 years in Finland ( Lyytikäinen et al, 2008b ).…”
Section: Discussionmentioning
confidence: 99%
“…Genital chlamydia trachomatis (CT) infection is the most common, curable sexually transmitted disease (STD) worldwide ( Woodhall et al, 2018 ). As up to 80% of cases are asymptomatic, CT infection often remains undetected or not diagnosed, which in turn results in the wide spread and delayed treatment of CT infection ( Marcone et al, 2012 ). Furthermore, untreated CT infection can cause scarring of the upper reproductive tract in women and lead to serious complications, such as pelvic inflammatory disease, ectopic pregnancy, and tubal factor infertility ( Haggerty et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation